In search of a constructionist theory of contemporary journalism - Gadini, Sérgio Luiz (2008)
This article discusses and explores some possible relationships between the perspective that comprises journalism as a unique form of knowledge production (Adelmo Genro Filho, 1988) and the constructionist approach to journalistic production (Gaye Tuchmann, 1983 and 1993, and Nelson Traquina, 1993 and 2001). In an articulated dialogue between comments, critiques and observations of several authors that thematize journalism, the author supports the idea that the potential of journalistic production lies in its uniqueness of daily action and, therefore, in the institutional dimension of the relations and events that mark the Contemporary social reality.